Recent progress and challenges in hollow fiber membranes for wastewater treatment and resource recovery - Rosmawati, Naim; Goh, Pei Sean; Zinnirah, Nasir; Nadzirah, Mohd Mokhtar; Nor Amirah Safiah, Muhammad (MDPI, 2021)
Membrane processes have been extensively employed in diverse applications, specifically in industrial wastewater treatment. The technological development in membrane processes has rapidly advanced and accelerated beyond its common principle and operation. Tremendous efforts have been made in the advancement of membrane materials, fabrication method, membrane modification and integration with other technologies that can augment the existing membrane processes to another level. This review presents the recent development of hollow fiber membranes applied in wastewater treatment and resource recovery. The membrane working principles and treatment mechanism were discussed thoroughly, with the recent development of these hollow fiber membranes highlighted based on several types of membrane application. The current challenges and limitations which may hinder this technology from expanding were critically described to offer a better perspective for this technology to be adopted in various potential applications.